Recognizing indigenous knowledge of the Karangwangi Rural Landscape in South Cianjur, Indonesia for sustainable land management - FATIYA AMELIA; JOHAN ISKANDAR; RUHYAT PARTASASMITA; NICHOLAS MALONE (Biodiversitas Journal of Biological Diversity, 2018)
Amelia F, Iskandar J, Partasasmita R, Malone N. 2018. Recognizing indigenous knowledge of the Karangwangi Rural Landscape in South Cianjur, Indonesia for sustainable land management. Biodiversitas 19: 1722-1729. Karangwangi is a rural community on the south coast of West Java, Indonesia. The people of Karangwangi possess traditional ecological knowledge (TEK) of local landscapes through cultural inheritance and personal experiences of interacting with their environment. The people of Karangwani Village recognize various natural-cultural landscape types, including leuweung (forest); swidden field (huma); wet rice fields (sawah); home garden (pekarangan); garden (kebun); mixed-garden (kebun campuran); river (sungai); and sea (laut). These various landscapes have continuously changed over time due to people’s socio-economic and cultural activities. The aim of this study was to develop an ethnoecological approach to elucidate historical changes to the Karangwangi landscapes. Toward this aim, we conducted mixed-method, qualitative and quantitative research. In addition to recognizing the various types of cultural and natural landscapes, the local people of Karangwangi are able to describe the history of landscape changes between 1950 to 2017. As identified by informants, these changes have been caused by various factors, including increases in population density, implementation of government policies and village development.